Windthrows increase soil carbon stocks in a central Amazon forest - dos Santos, Leandro T.; Marra, Daniel Magnabosco; Trumbore, Susan Elizabeth; Camargo, Plínio Barbosa de; Negrón-Juárez, Robinson I.; Lima, Adriano José Nogueira; Ribeiro, Gabriel Henrique Pires de Mello; Santos, Joaquim dos; Higuchi, Niro (Biogeosciences, 2016)
Windthrows change forest structure and species composition in central Amazon forests. However, the effects of widespread tree mortality associated with wind disturbances on soil properties have not yet been described in this vast region. We investigated short-term effects (7 years after disturbance) of widespread tree mortality caused by a squall line event from mid-January of 2005 on soil carbon stocks and concentrations in a central Amazon terra firme forest. The soil carbon stock (averaged over a 0-30 cm depth profile) in disturbed plots (61.4 ± 8.2 Mg ha-1, mean ±95 % confidence interval) was marginally higher (p = 0.09) than that from undisturbed plots (47.7 ± 13.6 Mg h-1). The soil organic carbon concentration in disturbed plots (2.0 ± 0.17 %) was significantly higher (p < 0.001) than that from undisturbed plots (1.36 ± 0.24 %). Moreover, soil carbon stocks were positively correlated with soil clay content (r2 = 0.332, r = 0.575 and p = 0.019) and with tree mortality intensity (r2 = 0.257, r = 0.506 and p = 0.045). Our results indicate that large inputs of plant litter associated with large windthrow events cause a short-term increase in soil carbon content, and the degree of increase is related to soil clay content and tree mortality intensity. The higher carbon content and potentially higher nutrient availability in soils from areas recovering from windthrows may favor forest regrowth and increase vegetation resilience. © Author(s) 2016.
Keywords: Carbon Sequestration; Clay Soil; Concentration (composition); Ecosystem Resilience; Forest Ecosystem; Mortality Risk; Nutrient Availability; Regrowth; Soil Carbon; Windthrow; Amazonia